National parks in the new legal and economic environment - Zawilińska, Bernadetta (Parki narodowe w nowych realiach prawnych i ekonomicznych, 2015)
The article presents the evolution of the legal environment and funding of national parks in Poland against worldwide trends in the funding of protected areas. Following transformations between 2010 and 2012, Polish national parks evolved from state budget entities into state-owned legal entities, largely autonomous in terms of organisation and finance. They have become visibly more active in raising funds for their own needs, be it through funded projects or business activities. Issues concerning sources of funding are discussed on the basis of the example of Babia Góra National Park. The Park’s “own funds” (raised through its own activity), mainly sale of wood, are its key budget item
Biblioteka Regionalisty, 2015, Nr 15, s. 113-122
Keywords: national parks; local development; public finances; parki narodowe; rozwój lokalny; finanse publiczne